Strategi Pengembangan Potensi Komoditas Pisang Cavendish Untuk Pertumbuhan Ekonomi Lokal Di Kabupaten Bondowoso - Holifah Holifah; Evita Soliha Hani; Sri Subekti; Luh Putu Suciati; Lenny Widjayanthi (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2026)
Banana production in Indonesia has increased year after year in line with population growth and economic development. Banana farming carries a high level of risk, including pest and virus attacks, unpredictable climate change, market risks, and low human resources. Bondowoso is one of the banana-producing regencies in East Java, and is among the top eleven banana producers in the region, with the potential to contribute raw materials for bananas. One banana that is increasingly growing and in high demand is the Cavendish banana. The banana production is marketed to PT Nusantara Segar Abadi (PT NSA) for further distribution outside the city, outside the island, and to the international market. However, Cavendish banana farmers still face various obstacles in marketing their crops to the company. This research aimed to: (1) To find out the comparative advantages of banana commodities in Bondowoso Regency, (2) To find out the competitive advantages of banana commodities in Bondowoso Regency, (3) To find out the sustainability and leveraging factors for developing a local banana-based economy and (4) To determine strategies for developing a local banana-based economy in Bondowoso Regency.. The study employed a descriptive quantitative method using RAPFISH analysis and to formulate a partnership sustainability strategy using SWOT analysis. The results showed that: (1) The results of the Location Quotient (LQ) analysis of sub-districts with an average LQ value greater than one were thirteen sub-districts out of a total of twenty-three sub-districts in Bondowoso Regency. This means that the LQ calculation based on land area indicators indicates that banana commodities have a comparative advantage in Bondowoso Regency. (2) The Proportional Shift (0.057) and Differential Shift (0) values were positive (+), indicating that the banana commodity sector plays an important role in the internal economy relative to the broader (external) economic system. (3) The sustainability status of local economic development is assessed across five dimensions, with an average Sustainability Index value of 81.23, categorized as highly sustainable. (4) The IFAS and EFAS scores each show a positive (+) value. The Strengths score is greater than the Weaknesses score, with a difference of (+) 0.58, and the Opportunities score is greater than the Threats score, with a difference of (+) 0.17. Therefore, the local economic development strategy falls between the Strengths and Opportunities (SO) strategies, namely in Quadrant I. Therefore, the analysis of local economic development in Bondowoso Regency uses Strategy (ST).